A Knowledge Map Study of an Application of a Smart Land Planning Free-Trade Zone and China’s Contribution - Penghao Ye; Huarong Zhang; Siyi Ma; Fang Yang; Yanan Li (Land, 2022)
The use of a free-trade zone (FTZ) has emerged as a smart land tool in increasing trading, attracting foreign investment, attempting financial openness and conducting other pilot economic reforms, which adds higher requirements for smart spatial planning, smart industry planning and smart management planning. However, no systematic analysis has been performed, making it difficult to provide deeper insights into FTZs. Thus, this study conducted bibliometric and visual analysis to identify the research status, new theories or practices, and potential future directions of FTZs based on 953 publications from the Web of Science Core Collection. The results show that there is a marked rise in the number of FTZ studies since 2013, which is the same year China authorized the first FTZ in Shanghai. China and the United States of America have played a leading role in FTZ research. Finally, the increasing trend in FTZ utilization will remain sizeable during its deepening development. The findings may contribute to a better understanding of FTZs and make some references to smart land-use planning experience and practices around the globe.